The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11104-020-04505-4
|View full text |Cite
|
Sign up to set email alerts
|

Root capacitance measurements allow non-intrusive in-situ monitoring of the seasonal dynamics and drought response of root activity in two grassland species

Abstract: Background and aims In this study, the potential of nonintrusive root electrical capacitance (C R) measurements for monitoring the seasonal changes and drought response of root activity was tested on two grassland species in a climate change experiment. Methods C R was detected between a ground electrode inserted into the soil and a plant electrode attached to the stem of the perennial grass Stipa borysthenica and the biennial herb Crepis rhoeadifolia in control and drought plots throughout two growing seasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Effects of acid on the root physiological resistance of L. perenne. Root activity directly affects the growth and development of plants (Cseresnyés et al 2020) and gives some insight into the tolerance of L. perenne to soil acid stress. The root activity of L. perenne was the lowest at pH 4.0 and significantly increased with greater soil pH.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of acid on the root physiological resistance of L. perenne. Root activity directly affects the growth and development of plants (Cseresnyés et al 2020) and gives some insight into the tolerance of L. perenne to soil acid stress. The root activity of L. perenne was the lowest at pH 4.0 and significantly increased with greater soil pH.…”
Section: Discussionmentioning
confidence: 99%
“…to drought) shares many similarities with the process of natural plant senescence at the end of the growing season (Gepstein and Glick, 2013;Sade et al, 2018). Furthermore, it has been reported that several plant species showed a significant accelerated maturity in response to water limitation (Desclaux and Roumet, 1996;Talukdar, 2013;Cseresnyeś et al, 2020). To create a drought, pallets of the 'autumn treatment' were covered for six weeks prior to the flume experiment to exclude rainfall while the 'summer treatment' pallets were kept irrigated with freshwater (Schoutens et al, 2021).…”
Section: Plant Materialsmentioning
confidence: 96%
“…In the case of grasses, drought also causes a decrease in leaf water content, photosynthesis, respiration and root activity [31][32][33], which may cause a decrease in biomass production [34] and impair the nutritive value of the hay [35].…”
Section: Introductionmentioning
confidence: 99%